(untitled) (Carnets Geol., 2024)
A new species, †Nannotanyderus granieri sp. nov., belonging to the Tanyderidae (Diptera, Nematocera), from Lower Barremian amber of Bqaatouta (Lebanon), is characterized, described, figured, and its taxononomic position discussed. The possible confusion regarding the attribution of new fossils to either the Tanyderidae or the Psychodidae, in addition to the results of recent molecular phylogenies, have led us to re-evaluate the taxonomic position of the Tanyderidae and to consider it as a subfamily within the Psychodidae. The fossil described herein is a tiny tanyderine sensu nov. species, and the second one belonging to the genus Nannotanyderus from Lebanese amber. A tentative molecular phylogeny of recent Psychodidae and an exhaustive catalogue of fossil Tanyderinae stat. nov. are provided.